2015
DOI: 10.1002/cphc.201500517
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Properties of Polynuclear Superhalogens without Halogen Ligand via ab Initio Calculations: A Case Study on Double‐Bridged [Mg2(CN)5]−1 Anions

Abstract: An ab initio study of the superhalogen properties of eighteen binuclear double-bridged [Mg2 (CN)5 ](-1) clusters is reported herein by using various theoretical methods. High-level CCSD(T) results indicate that all the clusters possess strong superhalogen properties owing to their high vertical electron detachment energies (VDEs), which exceed 6.8 eV (highest: 8.15 eV). The outer valence Green's function method provides inaccurate relative VDE values; hence, this method is not suitable for this kind of polynuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 80 publications
(128 reference statements)
0
15
0
Order By: Relevance
“…Polynuclear superhalogens (M n X n · k + 1 ), of which the number of central atoms ( n ) is larger than one, take advantage of increasing the number of ligands while maintaining their high stability and, therefore, exploring polynuclear superhalogens has become an essential novel research direction (see Refs. and references cited therein). Examples include magnesia halogens whose electron affinities do not only confirm their superhalogen nature but also reveal a strong relationship with the number of central metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Polynuclear superhalogens (M n X n · k + 1 ), of which the number of central atoms ( n ) is larger than one, take advantage of increasing the number of ligands while maintaining their high stability and, therefore, exploring polynuclear superhalogens has become an essential novel research direction (see Refs. and references cited therein). Examples include magnesia halogens whose electron affinities do not only confirm their superhalogen nature but also reveal a strong relationship with the number of central metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of superhalogens in the design and synthesis of new materials of technological importance has spurred considerable interest not only in expanding their scope but also in finding ways to enhance their electron affinities. Recent works have shown that superhalogens are not restricted to just a metal atom at the core surrounded by halogen atoms but can be created when the core atom is replaced by a cluster, when the ligands are no longer halogen atoms, and even when none of the constituents are metal or halogen atoms . Equally important, a new class of electronegative clusters called hyperhalogens has emerged where the halogen ligands are replaced by superhalogen ligands, enabling their electron affinities to surpass those of their superhalogen building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of discrepancies between their Outer Valence Green′s Function (OVGF) and coupled‐cluster singles and doubles plus approximate triples, or CCSD(T), calculations of the vertical detachment energies (VDEs) of six [Mg 2 (CN) 5 ] − isomers, Li et al. asserted that the former method is not suitable for this kind of superhalide . The results of Table and Figure demonstrate that this claim is false.…”
Section: Vdes Of [Mg2(cn)5]− Superhalides [Ev][a]mentioning
confidence: 99%
“…Dashed lines are for 2 A“ final states. Previous OVGF results obtained by Li et al with their TZ2 basis set are included for comparison.…”
Section: Vdes Of [Mg2(cn)5]− Superhalides [Ev][a]mentioning
confidence: 99%